2011
DOI: 10.1159/000321886
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy in Chronic Hepatic Disorders: Portal Vein Thrombosis and Improvement of Liver Function

Abstract: Background: Splenectomy is gaining increasing importance for cirrhotic patients with hypersplenism. However, its safety and efficacy for patients with chronic liver disease remain unclear. Methods: We retrospectively examined the medical records of 38 consecutive cirrhotic patients who underwent splenectomy or simultaneous hepatectomy and splenectomy for hepatocellular carcinoma. Results: White blood cell and platelet counts significantly increased 3 months after splenectomy. Serum levels of total bilirubin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 40 publications
4
63
0
1
Order By: Relevance
“…Liver function parameters have been often improved after splenectomy, in addition to the amelioration of thrombocytopenia in several clinical reports [3][4][5][6]; however the underlying mechanism remains unclear. To investigate the mechanism, an appropriate animal model resembling the clinical situation is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver function parameters have been often improved after splenectomy, in addition to the amelioration of thrombocytopenia in several clinical reports [3][4][5][6]; however the underlying mechanism remains unclear. To investigate the mechanism, an appropriate animal model resembling the clinical situation is required.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, splenectomy has been performed as a palliative surgical treatment to attenuate hypersplenism [1,2]. Recently, it has been reported that liver function parameters improved after splenectomy, in addition to the amelioration of thrombocytopenia in several clinical settings [3][4][5][6]. However, the mechanism underlying such a phenomenon remains unclear, and the significant role of platelets in liver fibrosis has been emphasized in some reports [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…810 Since it was first reported by Delaitre in 1991, 11 laparoscopic splenectomy (LS) has demonstrated distinct advantages compared with open splenectomy (OS), including shorter hospital stays, less blood loss, reduced costs, and better cosmetic outcomes; since then, it has been recommended as the standard procedure for benign hematological diseases, particularly for chronic immune thrombocytopenia (ITP). 12 Recently, a number of studies have clarified the feasiBILity, safety, and effectiveness of LS for hypersplenism caused by liver cirrhosis, suggesting that patients will benefit more in terms of short- and long-term surgical outcomes compared with OS.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the present study indicated that the amount of blood PLTs was significantly higher 2 weeks after the surgery (P<0.05), although the difference between the preoperative number of blood PLTs and those present one week later was not significant (P>0.05). The number of PLTs clearly increased, which led to the formation of portal vein thrombosis following splenectomy, with the rate of thrombosis up to 34.2% (32). Several of the patients required anticoagulant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The blood platelet (PLT) and white blood cell (WBC) counts decrease dramatically, with abnormal coagulation function. The traditional therapy for hypersplenism is splenectomy, and the preferred treatment of HCC is hepatectomy, so the treatment advocated from previous studies is hepatectomy combined with splenectomy (1)(2)(3)(4), although this procedure leads to severe coagulation disorder and lost immune function of the spleen; furthermore, the incidence of portal vein thrombosis is high following a splenectomy (5).…”
Section: Introductionmentioning
confidence: 99%